Application of Glyoxal Acrylamide Modified Κ-Carrageenan as A Superabsorbent Polymer in Drug Delivery System - Aji Prasetyaningrum; Al Farrel A. Raemas; Nur Rokhati; Bakti Jos (Dept. of Chemical Engineering, Diponegoro University, 2020)
The hydrogel is superabsorbent polymers (SAP) that are biodegradable and can be obtained from polysaccharides, lipids, and proteins. Polysaccharides include cellulose, starch and their derivatives, seaweed extracts such as carrageenan, alginate, pectin, and chitosan. Carrageenan is the result of the extraction of red seaweed sap with an alkaline solution. The main objective of this study was to simultaneously increase the strength and properties of κ-carrageenan SAP film with the addition of glyoxal and acrylamide as crosslinkers. The addition of acrylamide (variated from 1 to 7 % b/v) into the k-Carrageenan based SAP hydrogel compound and the presence of glyoxal as crosslink agent (variated from 0 to 1,0 % v/v). The physical properties of the SAP films were analyze using swelling degree and tensile strength. The structural and morphological properties of composite films were analyzed using Fourier Transform Infrared (FTIR) and Scanning Electron Microscopy (SEM). In addition, the effect of pHs on the releasing drug Poly(vinylpyrrolidone)-Iodine was investigated. This research shows that the addition of acrylamide and glyoxal can improve the physical properties of the modified κ-carrageenan film. Characterization using SEM shows that the addition of glyoxal causes the formation of tissue fibers in SAP. FTIR spectra indicated the formation of cross bonds in modified SAP film at 3294.42 cm-1 (carboxylic acid). The treatment under alkaline conditions will increase drug release ability.Keywords: κ-carrageenan; hydrogels; acrylamide; glyoxal; drug delivery